ETIKA KONSELING DALAM KONTEKS LINTAS BUDAYA DAN AGAMA - M MASRURI (Universitas Islam Negeri Mataram, 2016)
Religion and culture are two entities have always been inherent in human life as social beings. The synergy between religion and culture in affecting the life order of human becomes a uniqueness part in the plural society, the diversity of religion and culture in a society with each having belief, thought, paradigm, values, and norms. It becomes a challenge for counselors to have competence in the feld of cultural skills, in understanding the diversity of cultural values and religion. The urgency of that understanding is to avoid cultural bias and religion between counselor and counselee. Thus, the counselors are required to have a cultural sensitive and to develop tolerant attitude in the diverse of population, especially for counselors who work in educational settings. The diverse problem of religions and cultures become problems, which often appear on the surface, such as the harassment of religious teachings, traditions, gender issues.